Tingkat Kebugaran Fisik dan Gangguan Kognitif Lansia Usia 60-70 Tahun yang Mengikuti Senam Tai Chi - Rahmatul Laili Salsabillah; Noortje Anita Kumaat; Heri Wahyudi; Achmad Widodo (Mutiara Pendidikan dan Olahraga, 2025)
Elderly aged 60-70 years will experience changes in body condition, both physical and mental changes such as decreased physical fitness and cognitive disorders. This study aims to determine the level of fitness and cognitive disorders of elderly aged 60-70 years who participate in Tai Chi gymnastics. The method used is descriptive analytical with a Cross Sectional approach. The subjects of the study were 20 elderly aged 60-70 years, using a purposive sampling technique. The data collection technique for physical fitness levels was measured through the Six minutes walk test, while cognitive disorders used the mini-mental state examination (MMSE) questionnaire. The results of the study showed that the average level of male fitness was in the moderate fitness category (40.3%), the good category was (50%) and the very good category (6.3%), while female physical fitness was in the moderate fitness category (75%) and the very good category (25%). Research Results Cognitive disorders in elderly men who were in the normal category were 87.5% and probable cognitive disorders were 12.5%, while in elderly women cognitive disorders were in the normal category were 100%. In conclusion, the level of physical fitness of the elderly is in the good category, while cognitive disorders of the elderly are in the normal category